2019
DOI: 10.1080/15980316.2019.1704895
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive effect on image quality in full ultra-high definition(8 K)

Abstract: Resolution for displays are increasing from 4K-UHD to 8K-Full UHD. We conducted a subjective image quality evaluation to compare the image quality between 4 and 8 K by using diverse image stimuli. As a result, we identified perceptual and cognitive characteristics that can be demonstrated in image quality above 8 K. Cognitive and synesthetic factors as well as perceptual factors, and color expression were improved in 8 K image quality. The research findings suggested that both perceptual and cognitive factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…These studies suggest that UHD resolution can have various psychological effects on the viewers, even beyond the design viewing distance. Park et al performed paired comparison between 8K and 4K images on 65-inch displays at a viewing distance of 2.74 m [15]. They established that 8K resolution images were perceived to be better with respect to all the assessment items, except "brightness" and "fatigue.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies suggest that UHD resolution can have various psychological effects on the viewers, even beyond the design viewing distance. Park et al performed paired comparison between 8K and 4K images on 65-inch displays at a viewing distance of 2.74 m [15]. They established that 8K resolution images were perceived to be better with respect to all the assessment items, except "brightness" and "fatigue.…”
Section: Related Workmentioning
confidence: 99%
“…This scheme facilitated an understanding of the latent relationship between higherand lower-order impressions. Another study [15] also followed a similar scheme and attempted to elucidate the relationships. With this scheme, we found that the increase in the resolution of the presented images enhanced the impressions, even when the viewing distance was four times more than the design viewing distance.…”
mentioning
confidence: 99%
“…Realness is the similarity of the reproduction from the original real object. Also, the depth information increases providing realness of the whole situation of the scene within the whole image [3]. Also, studies have reported that the three-dimensional effect is noticeable in images exceeding normal resolution (60cpd) [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, it still feels bright and clear. Increased resolution has affected the contrast and recognition of displays, and studies show that unlike actual measurements, there is a higher awareness of contrast and color contrast as resolution increases [1,2]. In addition, the brightness and driving method of the display, along with its resolution, can function as a factor that can affect brightness recognition and image quality recognition.…”
Section: Introductionmentioning
confidence: 99%